2020
DOI: 10.1007/s00240-020-01204-8
|View full text |Cite
|
Sign up to set email alerts
|

Oral chemolysis is an effective, non-invasive therapy for urinary stones suspected of uric acid content

Abstract: Despite the possible benefit from avoiding stone surgery with all its possible complications, oral chemolysis is rarely performed in patients with urinary stones suspected of uric acid content. Among the reasons for its limited use is the sparse and low-quality data on its efficacy and the lack of reliable factors predicting its outcome. We thus performed a retrospective single-center cohort study of 216 patients (median patient age 63 years) with 272 renal (48%) and/or ureteral (52%) stones treated with oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 26 publications
(39 reference statements)
0
17
0
1
Order By: Relevance
“…Oral dissolution therapy was associated with a stone-free rate of 16% in 1 month and 50% in 3 months [128 & ]. Likewise, three nonrandomized recent studies have reported 3 months stone free rates of 61-64% [129,130] as well as a 6 months stone free rate of 83% [131]. Patient selection factors associated with response included smaller stones, lower density, and lower HUD [129][130][131].…”
Section: Compositionmentioning
confidence: 99%
“…Oral dissolution therapy was associated with a stone-free rate of 16% in 1 month and 50% in 3 months [128 & ]. Likewise, three nonrandomized recent studies have reported 3 months stone free rates of 61-64% [129,130] as well as a 6 months stone free rate of 83% [131]. Patient selection factors associated with response included smaller stones, lower density, and lower HUD [129][130][131].…”
Section: Compositionmentioning
confidence: 99%
“…For example, calcium oxalate monohydrate (COM [or Ia]), or calcium oxalate dihydrate (COD [or IIb]), criteria would support the prescription of an immediate diet containing potassium citrate, as reported in Soyg€ ur et al [10]. Recognition of uric acid (UA [or IIIb]) morphological criteria would steer the medical decision towards postoperative urinary alkalinization with potassium citrate or sodium bicarbonate to dissolve residual fragments [11].…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ]. Recognition of uric acid (UA [or IIIb]) morphological criteria would steer the medical decision towards postoperative urinary alkalinization with potassium citrate or sodium bicarbonate to dissolve residual fragments [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Distinguishing UA from non-UA stones is of particular interest for the urologist, as the former can be treated with alkalization of the urine, allowing for secondary prophylaxis after ex vivo composition analysis of a passed or surgically removed stone [4][5][6][7]. Ideally, a UA stone is identified and dissolved in vivo, to facilitate stone passage and obviate surgical removal [8,9]. At present, in vivo stone composition analysis is mostly accomplished with dual-energy CT (DE-CT), which has shown high accuracy in several studies [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…It is highly reproducible for measuring stone size and useful for predicting spontaneous stone passage [ 6 , 14 , 16 ]. If, in addition, this method could also predict the composition of the stone, the patient would be able to leave the emergency room with a tailored treatment on the first day of radiologic diagnosis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%